2006
DOI: 10.1212/01.wnl.0000222734.56412.17
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation correlates with severity in Huntington disease

Abstract: These [(11)C](R)-PK11195 PET findings show that the level of microglial activation correlates with Huntington disease (HD) severity. They lend support to the view that microglia contribute to the ongoing neuronal degeneration in HD and indicate that [(11)C](R)-PK11195 PET provides a valuable marker when monitoring the efficacy of putative neuroprotecting agents in this relentlessly progressive genetic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
245
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(260 citation statements)
references
References 34 publications
13
245
0
2
Order By: Relevance
“…51 In vivo evidence of increased [ 11 C](R)-PK11195 binding in the striatum and cortical regions in symptomatic HD patients compared with healthy controls has been recently published. 52 In that study, [ 11 C](R)-PK11195 binding correlated with clinical severity of HD rated with Unified HD Rating Scale motor scores, and inversely with the level of striatal dopamine D2 receptor loss as assessed by [ 11 C]raclopride PET. The authors also reported that increased striatal [ 11 C](R)-PK11195 binding was present in a few presymptomatic HD gene carriers.…”
Section: Movement Disordersmentioning
confidence: 88%
“…51 In vivo evidence of increased [ 11 C](R)-PK11195 binding in the striatum and cortical regions in symptomatic HD patients compared with healthy controls has been recently published. 52 In that study, [ 11 C](R)-PK11195 binding correlated with clinical severity of HD rated with Unified HD Rating Scale motor scores, and inversely with the level of striatal dopamine D2 receptor loss as assessed by [ 11 C]raclopride PET. The authors also reported that increased striatal [ 11 C](R)-PK11195 binding was present in a few presymptomatic HD gene carriers.…”
Section: Movement Disordersmentioning
confidence: 88%
“…Microglial activation also demonstrated both temporal and spatial correlations with neuronal damage and dysfunction. Importantly, microglial activation and brain inflammation was associated with the severity in the progression of the disease [18]. Increased levels of IL-8 have been reported in HD brain [19] and in post-mortem samples from HD patients [20].…”
Section: Il-8 In Other Neurodegenerative Diseases Huntington's Diseasmentioning
confidence: 96%
“…Increased brain binding of 11 C-PK11195 was observed in several acute neurological and neurodegenerative disorders such as strokeinduced brain injury, multiple sclerosis, glioma, refractory epilepsy, AD and HD [8][9][10][11][12][13]. Increased uptake of 11 C-PK11195 was also reported in frontotemporal lobar degeneration [14] and HD [15]. In preclinical HD, regional brain atrophy and increased levels of microglial activation in the associative striatum areas (AST) correlated with HD onset [13].…”
Section: Translocator Protein Systemmentioning
confidence: 97%